2004
DOI: 10.1016/s0736-0266(03)00156-6
|View full text |Cite
|
Sign up to set email alerts
|

NF‐kB signaling blockade abolishes implant particle‐induced osteoclastogenesis

Abstract: In this study we investigated the effect of NF‐kB signaling blockade on polymethylmethacrylate (PMMA) particle‐induced osteoclastogenesis in vitro. We first established effective blockade of NF‐kB activity as tested by electrophoretic mobility shift assays (EMSA). Particle‐induced NF‐kB activation in murine osteoclast precursor cells (CSF‐1‐dependent bone marrow macrophages) was markedly reduced by co‐treatment of the cells with the NF‐kB inhibitors N‐tosyl‐L‐phenylalanine chloromethyl ketone (TPCK) and Calpai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 35 publications
5
88
1
Order By: Relevance
“…Interestingly, RANKL was upregulated (1.1-fold) and OPG was downregulated (1.4-fold), suggesting increased RANKL/ OPG (2-fold). Additionally, several signaling pathways known to affect osteoclastogensis were upregulated (eg, NF-kB (43) and interleukin 6 signaling). (42) Similar to our findings, Ju and colleagues described the presence of microenvironmental changes in the bone marrow of Terc À/À mice that limited the engraftment of transplanted wild-type hematopoietic stem cells owing to increased production of a number of cytokines, including granulocyte colony-stimulating factor (G-CSF).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RANKL was upregulated (1.1-fold) and OPG was downregulated (1.4-fold), suggesting increased RANKL/ OPG (2-fold). Additionally, several signaling pathways known to affect osteoclastogensis were upregulated (eg, NF-kB (43) and interleukin 6 signaling). (42) Similar to our findings, Ju and colleagues described the presence of microenvironmental changes in the bone marrow of Terc À/À mice that limited the engraftment of transplanted wild-type hematopoietic stem cells owing to increased production of a number of cytokines, including granulocyte colony-stimulating factor (G-CSF).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that the calpain-calpastatin system is involved in pre-osteoblastic proliferation and differentiation (25), its function in the regulation of RANKL-supported osteoclastogenesis remains unclear. To date, it has been only weakly suggested to play a part in implant particle-induced osteoclastogenesis (26).…”
mentioning
confidence: 99%
“…16,19,20 Further evidence suggests that activation of the transcription factor NF-kB appears to be central to particle induction of both pathways, that is, TNF and RANKLmediated osteoclastogenesis. 1,18,34,35 Other studies investigating signal transduction by osteoclasts have documented that TNF family members strongly induce MAP kinase-related pathways including c-Jun/JNK and ERKs, 15 as evident by using TNF-receptor compromised mice. 36 The complex response to PMMA particles that involves multiple cytokines and triggers multiple pathways prompted us to further delineate the role of a key pro-inflammatory pathway, namely the JNK pathway, in PMMA-induced signaling in osteoclast precursors and its role in particle-stimulated osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,18 Particles were rinsed in ethanol four times, sterilized in ethanol overnight, and then rinsed four times with PBS. Particles were resuspended in serum-free MEM and stored at À208C.…”
Section: Polymethylmethacrylate Particlesmentioning
confidence: 99%
See 1 more Smart Citation